Javanese Tradisional Healing Dalam Pemulihan Pasca Persalinan Pada Ibu Bersalin Normal Di Era Moderen - Yunia Renny Andhikatias; Megayana Yessy Maretta; Nurul Devi Andriani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: Postpartum care which can be handled by complications such as the entry of germsinto the uterus, both exogenously and endogenously. One form of treatment for postpartum motherswho adhere to the old culture is consuming herbal remedies, either homemade or factory-made. Jamuwhich is a traditional herb, has been widely accepted in almost all countries in the world. According toWHO, countries in Africa, Asia and Latin America use traditional herbal medicine as a complement toprimary medicine. Apart from herbal medicine, other postpartum treatments from Java are bengkung,pilis and massage. Objective: To find out whether Javanese Traditional Healing has significantbenefits for informants in the postpartum recovery process. Benefit: It is hoped that this study will bea reference in postpartum treatment. Research Method: Qualitative study of phenomenology. Thesampling technique used purposive random sampling. With the number of key informants as many as5 people. Data obtained by interviewing 5 key informants and 4 triangulation informants. Results: Theresults showed that all of the informants performed Javanese Traditional Healing. 4 informants drankthe herbal medicine carrying, did massage, used bengkung and pilis, while 2 informants drank the 40-day herbal sachet specifically for the postpartum period, performed massages and used curves.During consuming herbal medicine, doing massage and wearing curves, information states that her breast milk is getting heavier, her body is fit, sleep quality improves and her weight slowly returns tonormal. No complaints were made. Conclusion: The composition of the herbal medicine consumedby the informants can provide a smoothing effect of breastfeeding and make the body of the infomanfresher and maintain body weight coupled with postpartum massage which is carried out afterchildbirth. Meanwhile, Bengkung does not believe in maintaining the shape of the stomach andsupports the spine so that it is not sore.Keywords: Jamu, Traditional, Massage, Bengkung, Postpartum, Postpartum